Individualized multimodal treatment strategy for anaplastic thyroid carcinoma—Case report of long-term remission and review of literature. (2016) - Eckhardt, S.; Hoffmann, S.; Damanakis, A.I.; Di Fazio, P.; Pfestroff, A.; Luster, M.; Wunderlich, A.; Bartsch, D.K.
Highlights: The prognosis of anaplastic thyroid cancer (ATC) is poor with a mean survival time of six months following diagnosis. A generally accepted and effective treatment strategy for ATC has not been established yet. Pre-therapeutic in vitro investigation of novel drugs could succeed for a personalized antitumor therapy in patients affected by ATC. Individualized tumor therapy gives explanation concerning the mechanisms regulating the biology of ATC. In vitro drug evaluation of individual tumor cells might be a promising tool to ameliorate the prognosis of ATC patients. Abstract: Introduction: The prognosis of anaplastic thyroid cancer (ATC) is poor with a mean survival time of six months following diagnosis. Despite various attempts to modify common treatment modalities including surgery, external beam radiation and chemotherapy, an effective treatment is not available yet. We report, here, a patient who achieved long-term survival based on multimodal treatment, including in vitro evaluation of drug response of his tumor cells. Presentation of case: A 42 years old male patient underwent total thyroidectomy with central and lateral neck dissection for ATC (pT4b, pN0 (0/36), L0, V0, Pn1, R0 cM0 – UICC-Stage: IV b). From the tumor tissue a primary cell culture was established. While the patient received a combined radio-chemotherapy cell viability assays were performed using Sorafenib, Vandetanib und MLN8054 (Aurora kinase inhibitor) as inhibitors. Cell viability was determined by MTT-assay after 72 and 144 h of treatment. Discussion: All the three compounds affected cell viability in a time- and dose dependent manner. These effects were most pronounced by Sorafenib. Based on in vitro findings, the patient was treated daily with 400 mg Sorafenib for 75 days. 43 months after initial diagnosis, the patient had no evidence of disease as shown by MRI, CT and FDG-PET-CT imaging. Conclusion: In the setting of multimodal treatment, in vitro drug evaluation of individual tumor cells of patients might be a promising tool to ameliorate the fatal prognosis of selected ATC patients.